$3 billion per year would allow 100 million children to live free of malnutrition - International Food Policy Research Institute (International Food Policy Research Institute, 2013)
Infographic explaining that $3 billion per year (less than 5% of development assistance budget) would allow 100 million children to live free of malnutrition.